Therapeutic success in a case of toxic epidermal necrolysis with dramatic course - Silny, Wojciech; Dańczak-Pazdrowska, Aleksandra; Smuszkiewicz, Piotr; Duś-Żuchowska, Monika; Trojanowska, Iwona (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2010)
Toxic epidermal necrolysis (TEN) is a severe, potentially fatal, predominantly drug-induced disease characterized by extensive damage of stratified squamous epithelium followed by loss of its integrity. To date over 100 medications related to TEN manifestation have been described. Methods of treatment are still a matter of great controversy due to inability to perform double-blind, placebo-controlled studies. In the paper the case of a 26-year-old man with TEN involving 100% of the body surface area, transferred to a specialist department after 7 days’ duration of disease, is described. The causative factor was difficult to establish. Combined treatment with high doses of glucocorticosteroids, cyclosporin A and plasmapheresis were administered. Despite the severe state of the patient at admission, therapeutic success was achieved due to administration of combined treatment. In our opinion, crucial for therapeutic success is early administration of aggressive systemic treatment whose activity includes the greatest possible number of elements involved in the pathogenesis of this potentially lethal disease.